Cancer cell-derived IL-1α induces CCL22 and the recruitment of regulatory T cells. (1st September 2016) - Wiedemann, Gabriela Maria; Knott, Max Martin Ludwig; Vetter, Viola Katharina; Rapp, Moritz; Haubner, Sascha; Fesseler, Julia; Kühnemuth, Benjamin; Layritz, Patrick; Thaler, Raffael; Kruger, Stephan; Ormanns, Steffen; Mayr, Doris; et al.
ABSTRACT: In cancer patients, immunosuppression through regulatory T cells (Treg) is a crucial component of tumor immune evasion and contributes to disease progression. Tumor-infiltrating Treg in particular suppress local effector T cell responses and are associated with poor prognosis in tumors such as human pancreatic cancer or hepatocellular carcinoma (HCC). The chemokine CCL22 is known to recruit Treg into the tumor tissue and many types of human tumors are known to express high levels of CCL22. The mechanisms leading to intratumoral secretion of CCL22 are so far unknown. We demonstrate here that intratumoral CCL22 is induced in tumor-infiltrating immune cells through cancer cell-derived interleukin-1 (IL-1α). In pancreatic cancer and HCC, CCL22 is produced by intratumoral dendritic cells, while the cancer cells themselves do not secrete CCL22 in vitro and in vivo . Incubation of human peripheral blood mononuclear cells (PBMC) or murine splenocytes with tumor cells or tumor cell supernatants strongly induced CCL22 secretion in vitro . Tumor cell supernatants contained IL-1 and CCL22 induction in PBMC could be specifically prevented by the IL-1 receptor antagonist anakinra or by transfection of tumor cell lines with IL-1 siRNA, leading to a suppression of Treg migration. In conclusion, we identify here tumor cell-derived IL-1α as a major inducer of the Treg attracting chemokine CCL22 in human cancer cells. Therapeutic blockade of the IL-1 pathway could represent a promising strategy to inhibit tumor-induced immunosuppression.